2016
DOI: 10.3389/fphys.2016.00646
|View full text |Cite
|
Sign up to set email alerts
|

TGR5, Not Only a Metabolic Regulator

Abstract: G-protein-coupled bile acid receptor, Gpbar1 (TGR5), is a member of G-protein-coupled receptor (GPCR) superfamily. High levels of TGR5 mRNA were detected in several tissues such as small intestine, stomach, liver, lung, especially in placenta and spleen. TGR5 is not only the receptor for bile acids, but also the receptor for multiple selective synthetic agonists such as 6α-ethyl-23(S)-methyl-cholic acid (6-EMCA, INT-777) and a series of 4-benzofuranyloxynicotinamde derivatives to regulate different signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 87 publications
(124 reference statements)
2
140
0
2
Order By: Relevance
“…study, because EGCG increased the expression of Tgr5 and the concentration of TGR-5 agonists (i.e., TLCA and LCA), it is likely that EGCG activates TGR-5 and its associated signaling. This notion is also supported by the findings that EGCG increased the expression of TGR-5 target genes, including Dio2 and Nos1 (39). Moreover, consistent with our data that showed that WD-fed mice had reduced Dio2 in their visceral fat and ileum, patients with obesity also have reduced DIO-2 in their white adipose tissues (67).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…study, because EGCG increased the expression of Tgr5 and the concentration of TGR-5 agonists (i.e., TLCA and LCA), it is likely that EGCG activates TGR-5 and its associated signaling. This notion is also supported by the findings that EGCG increased the expression of TGR-5 target genes, including Dio2 and Nos1 (39). Moreover, consistent with our data that showed that WD-fed mice had reduced Dio2 in their visceral fat and ileum, patients with obesity also have reduced DIO-2 in their white adipose tissues (67).…”
Section: Discussionsupporting
confidence: 91%
“…Because of the significant change in BAs in the cecal content in response to EGCG supplementation, we studied TGR-5 and FXR signaling in different tissues. TGR-5induced Dio2 potentially can improve metabolism by generating thyroxine (39). In the liver, visceral fat, and ileum, WD intake reduced Tgr5 and Dio2 mRNA levels with the exception of ileal Tgr5.…”
Section: Egcg Regulates Tgr-5 and Fxr-mediated Signaling Pathwaysmentioning
confidence: 99%
“…To monitor TGR5 activity, we studied the expression of the Tgr5 gene as well as its downstream target. Activation of TGR5 induces type II iodothyronine deiodinase (Dio2) that generates thyroxine, a key player in basal metabolism [33]. In addition, BA-activated TGR5 stimulates nitric oxide production by inducing Nos3 in vascular endothelial cells [34].…”
Section: Effect Of Diet and Dermatitis Development On Tgr5 Signalingmentioning
confidence: 99%
“…TGR5 activation leads to an increase in cAMP and PKA activation and has been shown to modulate bile acid homeostasis and inflammation (4951). TGR5 has been detected in cholangiocytes, Kupffer cells, and sinusoidal endothelial cells but not hepatocytes (52).…”
Section: The Response Of Cholangiocytes To Cholestasismentioning
confidence: 99%